Co-simulation and Experiment Research on a Novel Erection Mechanism - FENG Jiangtao; HUANG Xianxiang; GAO Qinhe; GUO Xiaosong; YAO Xiaoguang (Universitas Ahmad Dahlan, 2016)
The erection mechanism with movable back hinged bearing is a novel erection mechanism and the form of its moving process is complicated. The novel erection mechanism needs to be extensively tested to prove its value and to ensure it works properly. Kinetic analysis was accomplished and mathematical model of the hydraulic system was acquired. Fuzzy adaptive PID control was adopted for the erection mechanism taking advantage of fuzzy control and PID control. The novel erection mechanism was validated by virtual prototype technology realized by co-simulation method. The mechanical, hydraulic and control models were respectively established in ADAMS, AMESim and Simulink. Experiment was completed on a platform. The results of simulation and experiment indicate that the novel erection mechanism can move based on designed scheme and the control effect of fuzzy adaptive PID control is excellent. The novel erection mechanism has great practical value.